2022
DOI: 10.3390/ani12202862
|View full text |Cite
|
Sign up to set email alerts
|

Medical Management versus PACK-CXL in Dogs with Infectious Keratitis: A Randomized Controlled Trial Protocol

Abstract: Infectious keratitis is a common and painful disease, usually caused by bacteria in dogs. Brachycephalic breeds are at increased risk. Despite medical therapy, enzymatic corneal melting can lead to ulcer perforation and globe loss. Treatment alternatives are needed due to an increase in antibiotic resistance and growing popularity of brachycephalic dogs. Photoactivated Chromophore for Keratitis-Corneal Cross-linking (PACK-CXL) reduces enzymatic collagenolysis and damages multiple targets within microorganisms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For example, povidone iodine has proven efficacy for treating human microbial keratitis 57,58 and N ‐acetylcysteine has demonstrated in vitro antimicrobial activity against three bacterial species commonly isolated from dogs with infectious keratitis 59 . Photoactivated chromophore for keratitis‐corneal crosslinking results has been demonstrated as a technique that results in non‐antibiotic‐based elimination of bacteria and further research into its efficacy is currently being undertaken 60,61 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, povidone iodine has proven efficacy for treating human microbial keratitis 57,58 and N ‐acetylcysteine has demonstrated in vitro antimicrobial activity against three bacterial species commonly isolated from dogs with infectious keratitis 59 . Photoactivated chromophore for keratitis‐corneal crosslinking results has been demonstrated as a technique that results in non‐antibiotic‐based elimination of bacteria and further research into its efficacy is currently being undertaken 60,61 …”
Section: Discussionmentioning
confidence: 99%
“…59 Photoactivated chromophore for keratitis-corneal crosslinking results has been demonstrated as a technique that results in non-antibiotic-based elimination of bacteria and further research into its efficacy is currently being undertaken. 60,61 Infected corneal ulcers in this study at the time of sampling were being treated with range of topical and systemic antimicrobial therapy prescribed by the referring veterinary surgeon. Our study demonstrated that over half of the ulcers being treated with a topical antimicrobial at the time of sampling had a positive culture, a figure that is comparable to other similar veterinary and human studies.…”
Section: Antibiotic Treatment Before Corneal Samplingmentioning
confidence: 99%